DESIGN ON INTELLIGENT WI-FI SENSOR NETWORK (Balkan Journal of Applied Mathematics and Informatics, 2021)
In this paper intelligent Wi-Fi sensor network is designed. The main task is to visualize, store and distribution of the signals from industrial sensors to internet network. The solution is based on a microcomputer connection to the sensor network. In the paper, first, are described the characteristics of the used hardware, and the results of the experimental work of the of the developed solution are given.